Expression of cdk4 and p16 in Oral Lichen Planus - Sinny Goel; Nita Khurana; Akanksha Marvah; Sunita Gupta (Stilus Optimus, 2015)
Objectives: The purpose of this study was to evaluate the expression of cdk4 and p16, the proteins implicated in hyperproliferation and arrest in oral lichen planus and to compare their expression in erosive and non-erosive oral lichen planus and with normal mucosa and oral squamous cell carcinoma. Material and Methods: Analysis of cdk4 and p16 expression was done in 43 erosive oral lichen planus (EOLP) and 17 non-erosive oral lichen planus (NOLP) cases, 10 normal mucosa and 10 oral squamous cell carcinoma (OSCC) cases with immunohistochemistry. Results: This study demonstrated a significantly increased expression of cytoplasmic cdk4 (80% cases, cells stained - 19.6%), and cytoplasmic p16 (68.3% cases, cells stained - 16.4%) in oral lichen planus (OLP) compared to normal mucosa. cdk4 was much higher in OSCC in both cytoplasm and nuclei compared to normal mucosa. Also, while comparing OLP with positive control, significant difference was noted for cdk4 and p16, with expression being more in OSCC. While comparing EOLP with NOLP; significant differences were seen for cdk4 cytoplasmic staining only, for number of cases with positive staining as well as number of cells stained. Conclusions: Overexpression of cytoplasmic cdk4 and p16 was registered in oral lichen planus, however considerably lower than in squamous cell carcinoma. Erosive oral lichen planus demonstrated overexpression of cytoplasmic cdk4 and premalignant nature compared to non-erosive lesion. Therefore there is an obvious possibility for cytoplasmic expression of cdk4 and p16 to predict malignant potential of oral lichen planus lesions.